Study of Domino Number Game Development for Early Childrens Ability to Recognize Numbers - Nur Ika Sari Rakhmawati; Rachma Hasibuan; Erni Lutfiyah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2019)
This study aims to develop and produce feasible and effective numerical domino game prototype used as learning to recognize symbols of number 1-10 for children aged 4-5 years. The design of study is research and development research adapted from Borg Gall research and development using Single one shot case study and One Pretest-Posttest Design Group. But the writers used only 9 steps. The subject in this study are Group A children aged 4-5 years in 6 kindergartens in Duduk sampeyan Subdistrict, Gresik District. Data were analyzed using descriptive quantitative. The results of this developmental research are numerical domino game prototype to develop 4-5 years old childrens ability to recognize number 1-10. The operational field testing stage shows The average score is 0.84, categorized as high. Therefore, it can be concluded that the numeric domino game is feasible and effective game used as learning to recognize the symbol of numbers 1-10 in children aged 4-5 years.